Factors Associated with Hemoglobinemia After 12 Months of Lucky Iron Fich (LIF) Use in Women of Reproductive Age (FAR, 15-49 years) in the Tambacounda Health District in 2020 (Senegal) - Diongue, Fatoumata Binetou; Bassoum, Oumar; Diallo, Amadou Ibra; Camara, Fatou; Dangoura, Ndiacé; Danfakha, Séga; Pene, Mor; Faye, Adama (British Journal of Healthcare and Medical Research, 2024)
Introduction: Senegal is one of the countries where food insecurity and malnutrition are major development challenges, the aim was to determine the factors influencing the increase in hemoglobinemia after Lucky Iron Fich (LIF) use. Methods: The methodological approach was based on a longitudinal, descriptive and analytical study between the results of the baseline (2019) and 12-month (2020) surveys. The population consisted of women aged 15 to 49 years who were followed up since 2019. Multiple linear regression modeling was performed with an alpha risk of 5%. Results: Of the 428 anemic women followed up, 34.0% were no longer anemic. The mean age was 28.4 years (+/-8.9). Almost half of the households (49.8%) lived in poverty. The mean hemoglobinemia was 10.1 (+/-2.3) g/dl, with values of 10.5 (+/-1.6 g/dl); 9.7 (+/-2.2 g/dl); 10.3 (+/-2.6 g/dl); and 9.8 (+/-2.5 g/dl) for the subgroups of LIF alone, LIF and livestock, LIF and farming, and no LIF at baseline. These means were statistically different from baseline in the response groups, except for the control group. The difference in hemoglobinemia was increased by 0.60 g/dl (p-value=0.04) with LIF and by 1.72 g/dl (p-value=0.02) with secondary education or higher. Conclusion: Lucky Iron Fish was effective in increasing hemoglobinemia after 12 months of use. It improved hemoglobinemia in FAR in the medium term.